Focal Point Evaluation of Energies for Tautomers and Isomers for 3-hydroxy-2-butenamide: Evaluation of Competing Internal Hydrogen Bonds of Types -OH horizontal ellipsis O=, -OH horizontal ellipsis N, -NH horizontal ellipsis O=, and CH horizontal ellipsis X (X=O and N) - BLEDA, ERDİ ATA; ALTUN, ZİKRİ (MDPI, 2021)
The title compound is a small molecule with many structural variations; it can illustrate a variety of internal hydrogen bonds, among other noncovalent interactions. Here we examine structures displaying hydrogen bonding between carbonyl oxygen and hydroxyl H; between carbonyl oxygen and amino H; hydroxyl H and amino N; hydroxyl O and amino H. We also consider H-bonding in its tautomer 2-oxopropanamide. By extrapolation algorithms applied to Hartree-Fock and correlation energies as estimated in HF, MP2, and CCSD calculations using the cc-pVNZ correlation-consistent basis sets (N = 2, 3, and 4) we obtain reliable relative energies of the isomeric forms. Assuming that such energy differences may be attributed to the presence of the various types of hydrogen bonding, we attempt to infer relative strengths of types of H-bonding. The Atoms in Molecules theory of Bader and the Local Vibrational Modes analysis of Cremer and Kraka are applied to this task. Hydrogen bonds are ranked by relative strength as measured by local stretching force constants, with the stronger =O horizontal ellipsis HO- > NH horizontal ellipsis O= > -OH horizontal ellipsis N well separated from a cluster > NH horizontal ellipsis O= approximate to >NH horizontal ellipsis OH approximate to CH horizontal ellipsis O= of comparable and intermediate strength. Weaker but still significant interactions are of type CH horizontal ellipsis N which is stronger than CH horizontal ellipsis OH.
Keywords: intramolecular hydrogen bonding; high-accuracy extrapolation methods; QTAIM; non-covalent interactions; local vibrational modes; CORRELATED MOLECULAR CALCULATIONS; SET MODEL CHEMISTRY; GAUSSIAN-BASIS SETS; ELECTRON-DENSITY; DISTANT ATOMS; PATHS; BORON